2019
DOI: 10.1108/sasbe-10-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting consumer buying behaviour of solar water pumping system

Abstract: Purpose The purpose of this paper is to identify the factors influencing farmers’ intention to purchase solar water pumping systems (SWPS). Design/methodology/approach The research is based on primary data that have been collected from a total of 345 solar pump users from different villages and rural areas of Punjab (India). Exploratory and confirmatory factor analysis and multiple regression analysis have been used to examine the collected data. Multiple regression analysis is used to examine the identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…People who are highly concerned about the environment are also of the view that preservation is the prime responsibility of the government itself (Farheen and Sehgal, 2018; Ministry of New and Renewable Energy, (MNRE), 2017). So it is very important for the government to justify its role by providing ample subsidies; and ultimately it will have an effect on the adoption of solar energy based products (Kumar et al , 2019; Horsky and Simon, 1983; Kalish and Lilien, 1983). Thus, keeping in mind its relevance it is imperative to consider this dimension to study the adoption decision for solar powered pumps.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…People who are highly concerned about the environment are also of the view that preservation is the prime responsibility of the government itself (Farheen and Sehgal, 2018; Ministry of New and Renewable Energy, (MNRE), 2017). So it is very important for the government to justify its role by providing ample subsidies; and ultimately it will have an effect on the adoption of solar energy based products (Kumar et al , 2019; Horsky and Simon, 1983; Kalish and Lilien, 1983). Thus, keeping in mind its relevance it is imperative to consider this dimension to study the adoption decision for solar powered pumps.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Around 4 billion liters of diesel is being consumed in the agriculture sector in the form of fuel for diesel based pumps (Ministry of New and Renewable Energy, (MNRE), 2017; Adelekan, 2012). In addition to this, erratic electricity supply and high costs are observed to be plausible challenges for farmers, resulting in poor irrigation and yield losses (Kumar et al , 2019; Ministry of New and Renewable Energy (MNRE), 2013). The crop yield improvement by 10 per cent can be made possible if an essential volume of water for irrigation is available as to when required (Pavel and Rajagopal, 2017; International Energy Agency, 2013; Sudha, 2011; Chen, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The first model analyzes the different alternatives according to the points of view of different actors. The multi-actor analysis is grounded in recent studies developed in the literature that have identified different user profiles, characterized by a different structure of preferences (Bottero et al , 2018a; Kumar et al , 2019). In the second model, it was decided to change the performance of the alternative solutions about the property value criterion so as to be able to explain the spatial phenomena related to energy efficiency appreciation.…”
Section: Identification Of the Evaluation Criteria And Definition Of The Preference Functionsmentioning
confidence: 99%
“…Environmentally conscious consumers are known as green consumers (Roberts, 1996;Hailes, 2007;Gandhi and Sheorey, 2019) and can be defined as one who demonstrates the act of buying or using products that are not injurious to the atmosphere (Kinnear et al, 1974;Kumar et al, 2019). Previous studies on green consumers have focused their actions that lessen the consumption of natural resources (Gardner and Stern, 2002;Jansson et al, 2010).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%